Method for manufacturing adhesive, adhesive body, and pressure-bonded body
By employing an adhesive with amorphous fluororesin and carbon dioxide in a non-heat-based bonding process, the challenges of heat resistance, contamination, and energy costs in substrate bonding are addressed, resulting in a strong, chemically resistant, and energy-efficient adhesive bond.
Patent Information
- Application Number
- JP2021567297
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-24
- Filing Date
- 2020-12-15
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2040-12-15
AI Technical Summary
Existing methods for bonding substrates, such as those using fluorine-based materials, face challenges with heat resistance, foreign matter contamination, limited substrate choice due to heat resistance requirements, and high energy costs associated with thermal fusion bonding.
The use of an adhesive containing amorphous fluororesin, which is applied in the presence of carbon dioxide in a liquid, gas-liquid mixed state, or near liquid state, allowing for bonding at temperatures below the melting point of the adhesive and substrates, thereby avoiding external heat and reducing energy costs.
This method achieves an adhesive with excellent chemical resistance, reduced risk of foreign matter contamination, flexible substrate selection, and maintains the shape and physical properties of the substrates before bonding, while also being energy-efficient and easy to process.
Smart Images

Figure 0007649513000001 
Figure 0007649513000002 
Figure 0007649513000003
Abstract
Description
[Technical field]
[0001] One embodiment of the present invention relates to a method for producing an adhesive, a bonded body, or a pressure-bonded body. [Background technology]
[0002] Substrates such as nonwoven fabrics, woven fabrics, fibers, porous membranes, and films may be used alone or in combination with a plurality of the same substrates or with other substrates.
[0003] When substrates are laminated in this manner, a method is usually used in which the substrates are bonded together using an adhesive by reacting components contained in the adhesive or volatilizing the solvent, or the substrates are bonded together by melting the adhesive layer or the substrate itself and heat fusing them.
[0004] The method of bonding substrates together using the adhesive has the advantage that the substrates can be bonded together easily, but the obtained bonded body may have problems with the heat resistance of the adhesive part, or foreign matter may be mixed in or contamination may occur at the adhesive part, leaving room for improvement in this regard.
[0005] In addition, the method of bonding substrates together by heat fusion has the advantage that an adhesive with high adhesive strength can be obtained, but the freedom of selection of the substrate is limited in terms of heat resistance, and there is room for improvement in that the shape and physical properties of the substrates before fusion, specifically, the shape of voids and the like that the substrates before fusion had, the function of the functional material contained in the substrates before fusion, and the functions of the substrates before fusion due to treatment such as surface treatment, are impaired (lost). Furthermore, the method of bonding substrates together by thermal fusion also leaves room for improvement in terms of energy costs.
[0006] As a method capable of solving the problems of the conventional bonding methods, Patent Document 1 discloses a method of bonding fibrous resin in the presence of carbon dioxide in a liquid state, a gas-liquid mixture state, or a state close to liquid. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2018-099885 A Summary of the Invention [Problem to be solved by the invention]
[0008] Fluorine-based materials are particularly excellent in chemical resistance and non-adhesiveness, and therefore the method described in Patent Document 1 does not disclose a method for bonding substrates together using such fluorine-based materials.
[0009] One embodiment of the present invention provides an adhesive that uses an amorphous fluororesin and is capable of forming an adherend having a desired shape and that is less susceptible to peeling between substrates. [Means for solving the problem]
[0010] As a result of intensive research by the present inventors to solve the above problems, it has been found that the above problems can be solved by the following configuration examples. A configuration example of the present invention is as follows.
[0011] [1] An adhesive containing an amorphous fluororesin for bonding substrates in the presence of liquid, gas-liquid or near-liquid carbon dioxide.
[0012] [2] The adhesive described in [1], which is an adhesive for bonding at a temperature below the melting temperature of the adhesive.
[0013] [3] The adhesive according to [1] or [2], wherein the amorphous fluororesin is a fluoropolymer having a fluorinated aliphatic ring (which may have an ether bond).
[0014] [4] An adhesive comprising two or more substrates bonded together with the adhesive according to any one of [1] to [3]. [5] The adhesive according to [4], wherein at least one of the substrates is a nonwoven fabric, a woven fabric, a porous membrane or a fiber.
[0015] [6] Two or more substrates, An adhesive containing an amorphous fluororesin; Carbon dioxide in liquid, gas-liquid mixture or near-liquid state A method for producing a crimped body, comprising step 1 of crimping in the presence of
[0016] [7] The step 1 A step 1a of contacting a laminate having an adhesive layer obtained from the adhesive between substrates with liquid or gaseous carbon dioxide and applying pressure; or a step 1b of contacting a contact body obtained by contacting a substrate with the adhesive or a dried body obtained by drying the contact body with liquid or gaseous carbon dioxide and applying pressure; The method for producing a pressure-bonded body according to [6], Effect of the Invention
[0017] According to one embodiment of the present invention, an adhesive body having a desired shape and in which peeling between substrates is unlikely to occur can be obtained by using an amorphous fluororesin. Furthermore, according to one embodiment of the present invention, in the obtained bonded body, the adhesive portion has excellent chemical resistance, is less susceptible to contamination or infiltration of foreign matter through the adhesive portion, allows for a high degree of freedom in the selection of the substrate, and is capable of maintaining the shape and physical properties of the substrate prior to bonding. Furthermore, according to one embodiment of the present invention, the bonded body can be formed without applying heat from the outside, so that the bonded body can be produced at low energy cost, and the obtained bonded body also has the advantage of being easy to subject to secondary processing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] <Adhesive> An adhesive according to one embodiment of the present invention (hereinafter also referred to as "the adhesive") is an adhesive used when bonding substrates in the presence of carbon dioxide in a liquid, gas-liquid mixed state, or near-liquid state, and contains an amorphous fluororesin.
[0019] Although it is not entirely clear why this adhesive can provide an adhesive body with the above-mentioned effects, it is thought that by adhering substrates in the presence of carbon dioxide in a liquid, gas-liquid mixture, or near-liquid state, the carbon dioxide plasticizes at least a portion of the amorphous fluororesin contained in the adhesive, allowing the substrates to be bonded and joined while their shape is fixed in an interlocking state due to an anchor effect, etc.
[0020] According to one embodiment of the present invention, an adhesive can be formed without the application of external heat, and therefore the adhesive is preferably an adhesive used when bonding substrates at temperatures below the melting points of the substrates and the adhesive, more preferably an adhesive used when bonding substrates at temperatures below about 50°C, and particularly preferably an adhesive used when bonding substrates without the application of external heat.
[0021] The adhesive of the present invention may be any adhesive used when bonding substrates in the presence of carbon dioxide in a liquid, gas-liquid mixed state, or near-liquid state. In this case, carbon dioxide in a subcritical or supercritical state may be present, but it is preferable that carbon dioxide in a subcritical or supercritical state is not present, since this allows for a reduction in pressing force and allows bonding without the use of a device having a heating mechanism, etc. The above-mentioned "carbon dioxide in a state close to liquid" specifically refers to carbon dioxide in a state in which the density is 0.4 g / mL or more (about half the density of liquid carbon dioxide).
[0022] [Amorphous fluororesin] The amorphous fluororesin is a resin containing fluorine atoms, has a completely amorphous structure, and is soluble in a specific fluorine-based solvent, and is preferably a perfluororesin in terms of being superior in the above-mentioned effects, etc. In particular, it is preferably a fluorine-containing polymer (hereinafter also referred to as "polymer (A)") having a fluorine-containing aliphatic ring (however, the ring may have an ether bond (-O-). The same applies below), and particularly preferably a fluorine-containing polymer having the fluorine-containing aliphatic ring in the main chain. The adhesive may contain two or more types of amorphous fluororesin.
[0023] Examples of the aliphatic ring include a saturated or unsaturated hydrocarbon ring which may have a substituent, and a heterocycle in which a part of the carbon atoms in the hydrocarbon ring are substituted with a heteroatom such as an oxygen atom or a nitrogen atom. Examples of the fluorine-containing aliphatic ring include rings in which a part or all of the hydrogen atoms in these rings are substituted with fluorine atoms. Among these, a heterocycle having one or two ether bonds in the ring skeleton is preferred, and further, a ring in which all of the hydrogen atoms in the heterocycle are substituted with fluorine atoms is more preferred.
[0024] Examples of the polymer (A) include a (co)polymer (A1) of at least one compound (I) selected from the compounds represented by the following formulas (1) and (2), and a copolymer (A2) of at least one compound (I) and at least one other monomer (II) selected from a diene-based fluorine-containing monomer, a monomer having a reactive functional group in the side chain, tetrafluoroethylene, chlorotrifluoroethylene, and perfluoro(methyl vinyl ether). The compound (I) is preferably one type of compound represented by the following formula (1), and the compound (II) is preferably tetrafluoroethylene, chlorotrifluoroethylene, or a diene-based fluorine-containing monomer, more preferably tetrafluoroethylene or a diene-based fluorine-containing monomer.
[0025] [ka]
[0026] In the formula, X 11 ~X 14 , Y 11 and Y 12 each independently represents a fluorine atom, a perfluoroalkyl group or a perfluoroalkoxy group. The perfluoroalkyl group and the perfluoroalkoxy group preferably have 1 to 7 carbon atoms, and more preferably 1 to 4 carbon atoms. X 11 As the group, a fluorine atom is preferable. X 12 is preferably a fluorine atom, a trifluoromethyl group, or a perfluoroalkoxy group having 1 to 4 carbon atoms, and more preferably a fluorine atom or a trifluoromethoxy group. X 13 and X 14 are each independently preferably a fluorine atom or a perfluoroalkyl group having 1 to 4 carbon atoms, and more preferably a fluorine atom or a trifluoromethyl group. Y 11 and Y 12 are each independently preferably a fluorine atom, a perfluoroalkyl group having 1 to 4 carbon atoms or a perfluoroalkoxy group having 1 to 4 carbon atoms, more preferably a fluorine atom or a trifluoromethyl group.
[0027] X 13 and X 14 may be bonded to each other to form a fluorine-containing aliphatic ring, Y 11 and Y 12 may be bonded to each other to form a fluorinated aliphatic ring. The fluorine-containing aliphatic ring is preferably a 4- to 6-membered ring, and is preferably a saturated aliphatic ring. The fluorine-containing aliphatic ring may have an ether bond in its ring skeleton, and in this case, the number of ether bonds is preferably 1 or 2.
[0028] Examples of the monomer having a reactive functional group in the side chain include methyl 2,2,3,3,4,4-hexafluoro-4-(1,2,2-trifluorovinyloxy)butanoate, methyl 2,2,3,3-tetrafluoro-3-(1,1,2,2,3,3-hexafluoro-3-(1,2,2-trifluorovinyloxy)propoxy)propanoate, methyl 1,1,2,2-tetrafluoro-2-(1,1,1,2,3,3-hexafluoro-3-(1,2,2-trifluorovinyloxy)propoxy)propanoate, and methyl 1,1,2,2-tetrafluoro-2-(1,1,1,2,3,3-hexafluoro-3-(1,2,2- Fluorine-containing monomers such as 1,1,2,2-tetrafluoro-2-(1,2,2-trifluorovinyloxy)ethanesulfonic acid fluoride and 1,1,2,2-tetrafluoro-2-(1,2,2-trifluorovinyloxy)ethanesulfonic acid fluoride; hydroxyethyl vinyl ether, hydroxypropyl vinyl ether, hydroxybutyl vinyl ether, 2-(2-(vinyloxy)ethoxy)ethanol, methyl acrylate, and hydroxyethyl acrylate.
[0029] The diene-based fluorine-containing monomer is preferably CF2=CFOCF2CF2CF=CF2 or CF2=CFOCF(CF3)CF2CF=CF2, and the former is more preferred.
[0030] The proportion of structural units based on compound (I) in the copolymer (A2) is preferably 20 mol % or more, more preferably 40 mol % or more, based on the total of all repeating units constituting the copolymer (A2).
[0031] Examples of the polymer (A) include a (co)polymer (A3) of at least one compound (III) selected from diene-based fluorine-containing monomers, and a copolymer (A4) of at least one compound (III) and at least one other monomer (IV) selected from compound (I), a monomer having a reactive functional group in a side chain, tetrafluoroethylene, chlorotrifluoroethylene, and perfluoro(methyl vinyl ether). The monomer (IV) is preferably tetrafluoroethylene or chlorotrifluoroethylene.
[0032] Specific examples of the diene-based fluorine-containing monomer include CF2=CFOCF2CF=CF2, CF2=CFOCF(CF3)CF=CF2, CF2=CFOCF2CF2CF=CF2, CF2=CFOCF2CF(CF3)CF=CF2, CF2=CFOCF(CF3)CF2CF=CF2, CF2=CFOCFClCF2CF=CF2, CF2=CFOCCl2CF2CF=CF2, CF2=CFOCF2OCF=CF2, CF2=CFOC(CF3)2OCF=CF2, CF2=CFOCF CF2=CFOCF2CF2CF=CF2, CF2=CFCF2CF2CF=CF2, CF2=CFCF2OCF2CF=CF2 are mentioned, and CF2=CFOCF2CF2CF=CF2, CF2=CFOCF2CF(CF3)CF=CF2, CF2=CFOCF(CF3)CF2CF=CF2, CF2=CFOCFClCF2CF=CF2, CF2=CFOCCl2CF2CF=CF2 and CF2=CFOCF2CF(OCF3)CF=CF2 are preferred.
[0033] The proportion of structural units based on compound (III) in the copolymer (A4) is preferably 50 mol % or more, more preferably 80 mol % or more, based on the total of all repeating units constituting the copolymer (A4).
[0034] The polymer (A) is preferably a polymer having a structure represented by the following formula (A2-1) or (A3-1).
[0035] [ka]
[0036] The polymer (A) may have a functional group such as a carboxy group, an alkoxycarbonyl group, an aminoalkyl group, a halogenocarbonyl group, an acid anhydride group, a hydroxy group, a sulfo group, an epoxy group, a cyano group, a carbonate group, an isocyanate group, an amide group, an aldehyde group, an amino group, a hydrolyzable silyl group, a carbon-carbon double bond, an alkoxy group, or an acyl group. The polymer (A) preferably has a hydrolyzable silyl group, in particular an aminosilane group.
[0037] The hydrolyzable silyl group is a group in which an alkoxy group, an amino group, a halogen atom, or the like is bonded to a silicon atom, and examples thereof include an aminosilane group (e.g., -CONH-C3H6-Si(OC2H5)3). Examples of the alkoxycarbonyl group include a methoxycarbonyl group, an ethoxycarbonyl group, a propoxycarbonyl group, an isopropoxycarbonyl group, a butoxycarbonyl group, and a tert-butoxycarbonyl group. Examples of the aminoalkyl group include an aminoethyl group and an aminopropyl group.
[0038] The weight average molecular weight (Mw) of the polymer (A) is preferably 50,000 or more, more preferably 150,000 or more, even more preferably 200,000 or more, and particularly preferably 250,000 or more, and is preferably 1,000,000 or less, more preferably 850,000 or less, even more preferably 650,000 or less, and particularly preferably 550,000 or less. When Mw is in the above range, it is easy to form a film, it is easy to dissolve in a solvent, and the film formation process is not easily restricted, which is preferable. In particular, when Mw is 200,000 or more, the thermal stability is excellent. The Mw is a value calculated from the intrinsic viscosity measured at 30° C. with a Ubbelohde viscometer using perfluoro(2-butyltetrahydrofuran) as a solvent, according to the formula described in Nippon Kagaku Kaishi, 2001, No. 12, p. 661.
[0039] The polymer (A) may be one obtained by synthesis based on a conventionally known method, for example, the method described in WO 2010 / 095554, or a commercially available product.
[0040] The content of the amorphous fluororesin relative to 100% by mass of the components other than the solvent and dispersion medium in the adhesive is preferably 90 to 100% by mass, more preferably 95 to 100% by mass, and particularly preferably 98 to 100% by mass. When the content of the amorphous fluororesin is within the above range, substrates can be easily bonded to each other in the presence of carbon dioxide in a liquid, gas-liquid mixed state, or near-liquid state, and an adherend having a desired shape and in which peeling between the substrates is unlikely to occur can be easily obtained. Furthermore, an adherend having excellent chemical resistance and in which foreign matter is unlikely to be mixed in or contaminated at the adhesive portion can be easily obtained.
[0041] In addition to the amorphous fluororesin, the adhesive may contain, as necessary, conventionally known additives such as anti-aging agents, antioxidants, processing aids (stearic acid, etc.), stabilizers, tackifiers, silane coupling agents, functional (nano)particles, plasticizers, flame retardants, waxes, lubricants, etc., within limits that do not impair the effects of the present invention.
[0042] Furthermore, when an adhesive obtained using this adhesive is used in a high temperature environment, there is a risk of volatilization, elution or precipitation, so it is preferable that the amount of the additives is as small as possible. Specifically, the amount is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 2 parts by mass or less, and particularly preferably 1 part by mass or less, per 100 parts by mass of amorphous fluororesin. It is even more preferable that no additives are contained.
[0043] The adhesive may be a solid adhesive in the form of a film, fiber, line, sphere (particle), lattice, nonwoven fabric, or the like, or may be a liquid adhesive in which the amorphous fluororesin or the like is dispersed or dissolved. In other words, the adhesive may contain a solvent capable of dispersing or dissolving the amorphous fluororesin, and in this case, it is preferable that the adhesive contains a solvent capable of dissolving the amorphous fluororesin. The concentration of the amorphous fluororesin in the liquid adhesive is preferably 0.3% by mass or more, more preferably 0.5% by mass or more, and is preferably 10% by mass or less, more preferably 3% by mass or less.
[0044] <Base material> There are no particular limitations on the substrate to which the adhesive of the present invention can be adhered, and examples include substrates containing at least one material selected from resins, carbon materials, glass, and metals. The substrate is preferably at least one selected from nonwoven fabric, woven fabric, porous membrane, and fiber, since it is possible to easily form an adhesive body having a desired shape in which peeling between substrates is unlikely to occur.
[0045] [resin] The resin is not particularly limited, but examples thereof include fluororesins, engineering plastics, and other plastics. Among these, fluororesins and engineering plastics are preferred.
[0046] [Fluorine resin] The fluororesin is not particularly limited, and any conventionally known fluororesin can be used. The amorphous fluororesin contained in the adhesive and the fluororesin constituting the substrate may be the same or different, but are preferably different, and it is more preferable that the crystallinity of the fluororesin constituting the substrate is higher than that of the amorphous fluororesin contained in the adhesive.
[0047] Specific examples of the fluorine-based resin include polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether copolymer (EPE), fluoroethylene-vinyl ether copolymer (FEVE), poly(chlorotrifluoroethylene) (PCTFE), ethylene-chlorotrifluoroethylene-copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), vinylidene fluoride-hexafluoropropylene copolymer (VDF-HFP copolymer), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer (VDF-HFP-TFE copolymer), etc. Among these, PTFE and PFA are preferred.
[0048] [Engineering plastics] The engineering plastic is not particularly limited, and conventionally known engineering plastics can be used. Specific examples of the engineering plastic include polyphenylene sulfide resin (PPS), polysulfone resin, polyethersulfone resin, polyetheretherketone resin (PEEK), polyarylate resin, liquid crystal polymer, aromatic polyester resin, polyimide resin, polyamideimide resin, polyetherimide resin, aramid resin, polycarbonate resin, polyacetal resin, polyester resin such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polycyclohexylene dimethyl terephthalate (PCT), polyphenylene ether resin, polyphenylene oxide resin, polyamide resin such as nylon 6, nylon 66, and aromatic polyamide, acrylic polymer, vinyl chloride polymer, vinylidene chloride polymer, polybenzoazole resin (e.g., polybenzimidazole (PBI)), polyethylene (e.g., ultra-high molecular weight polyethylene), and polypropylene (e.g., ultra-high molecular weight polypropylene).
[0049] [Other plastics] The other plastics are not particularly limited as long as they are resins other than fluorine-based resins and engineering plastics, and conventionally known plastics can be used.Specific examples of such plastics include thermosetting resins such as polyvinyl chloride (PVC), polystyrene (PS), acrylonitrile-butadiene-styrene resin (ABS), polymethyl methacrylate resin (PMMA), phenolic resins (including straight phenolic resins and various modified phenolic resins), melamine resins, and epoxy resins.
[0050] The substrate containing the resin may contain other components such as fibers, such as carbon fibers or glass fibers, and the additives described in the adhesive section.
[0051] Examples of the form of the substrate containing the resin include fibers, porous membranes (including stretched porous membranes), nonwoven fabrics, woven fabrics, and films. In addition, when a resin-containing film is used as the substrate, it is preferable to use a film whose surface in contact with the adhesive has been roughened by a conventionally known method, in order to obtain an adhesive body in which peeling between substrates is less likely to occur, etc. In addition, since it is not easy to bond resin-containing films together, when a resin-containing film is used as the substrate, it is preferable that the substrate to be bonded to the film is a substrate through which carbon dioxide can pass, such as a fiber, a porous membrane, a nonwoven fabric, or a woven fabric.
[0052] [Carbon materials] Examples of the substrate containing a carbon material include carbon fibers, carbon nanotubes, and graphite sheets. The shape of the carbon fibers is not particularly limited, and examples of the shape include fibers, filaments, cloth, felt, mats, papers, and prepregs.
[0053] [Glass] Examples of the substrate containing glass include glass fiber, glass woven fabric, and glass nonwoven fabric. Specific examples of these include glass cloth, glass paper, glass mat, glass felt, and substrates having the above-mentioned resin on the surface thereof.
[0054] [metal] Examples of the substrate containing a metal include woven fabric, nonwoven fabric, and metal fiber (including wool-like metal). The substrate containing a metal may also be a substrate in which a support such as a fiber, a porous membrane, a nonwoven fabric, or a woven fabric is treated with a metal (e.g., a substrate in which a support is plated, or a substrate in which a metal is vapor-deposited on a support). Examples of the metal include stainless steel, aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, copper, copper alloys, gold, gold alloys, silver, silver alloys, tantalum, tantalum alloys, chromium, chromium alloys, molybdenum, molybdenum alloys, tungsten, and tungsten alloys.
[0055] As the substrate, a substrate made of a fluororesin is preferable, and a substrate made of PTFE, PFA, or the like is more preferable, because the substrate has excellent mechanical strength, heat resistance, chemical resistance, weather resistance, and electrical insulation, and an adhesive can be easily obtained in which all of the components constituting the adhesive are fluorine components. Incidentally, since fluorine components are non-adhesive and have a small coefficient of friction, it has not been possible to obtain an adhesive having a desired shape that is less susceptible to peeling between the substrates when the adhesive is made entirely of fluorine components. However, according to one embodiment of the present invention, even when using an adhesive made of such fluorine components, it is possible to easily obtain an adhesive having a desired shape that is less susceptible to peeling between the substrates.
[0056] The nonwoven fabric, woven fabric, porous membrane, fiber (tube), and film (sheet) are not particularly limited, and conventionally known nonwoven fabrics, woven fabrics, porous membranes, fibers (tubes), and films (sheets) can be used.
[0057] The substrate may be a substrate that has been subjected to a functionalization treatment such as a conventionally known surface treatment such as a hydrophilization treatment. According to one embodiment of the present invention, even if a substrate that has been subjected to such a functionalization treatment is used, it is possible to form an adhesive body without impairing the function.
[0058] The fibers constituting the nonwoven fabric or woven fabric, or the average fiber diameter of the fibers, is preferably 0.01 μm or more, more preferably 0.1 μm or more, even more preferably 0.2 μm or more, and is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 20 μm or less. When the average fiber diameter is within the above range, an adhesive body having excellent mechanical strength and a desired shape that is less susceptible to fraying of fibers or peeling between substrates can be easily obtained.
[0059] The average fiber diameter is an average value calculated based on the measurement results by observing the fiber (group) to be measured with a scanning electron microscope (SEM) (magnification: 2000 times), randomly selecting 20 fibers from the obtained SEM image, and measuring the fiber diameter (long diameter) of each of these fibers.
[0060] The fiber diameter variation coefficient of the fibers constituting the nonwoven fabric or woven fabric, or of the fibers, calculated by the following formula, is preferably 0.7 or less, more preferably 0.01 or more, and more preferably 0.5 or less. When the fiber diameter variation coefficient is within the above range, the fiber diameter becomes uniform, and an adherend having a desired shape with excellent mechanical strength and with less tendency for fraying of the fibers or peeling between the substrates can be easily obtained. Coefficient of variation of fiber diameter = standard deviation / average fiber diameter (Note that the "standard deviation" refers to the standard deviation of the fiber diameters of the 20 fibers.)
[0061] The fibers constituting the nonwoven fabric or woven fabric and the fiber length of the fibers are not particularly limited, but are preferably 0.5 mm or more, more preferably 1 mm or more, and are preferably 100 mm or less, more preferably 50 mm or less.
[0062] The stretched porous membrane is not particularly limited, and may be a uniaxially stretched porous membrane or a biaxially stretched porous membrane.
[0063] The porosity of the nonwoven fabric, woven fabric or porous membrane is not particularly limited, but is, for example, 0.1 vol. % or more, preferably 30 vol. % or more, and is, for example, 95 vol. % or less, preferably 90 vol. % or less. The porosity can be calculated from the difference between the theoretical volume calculated assuming no voids based on the specific gravity of the material constituting the nonwoven fabric, woven fabric or porous membrane and the actual measured mass of the nonwoven fabric, woven fabric or porous membrane, and the actual volume calculated by measuring the dimensions of the nonwoven fabric, woven fabric or porous membrane, using the following formula. Porosity (volume%) = (1-(theoretical volume / measured volume)) x 100
[0064] The weight of the nonwoven fabric, woven fabric or porous membrane is preferably 100 g / m 2 More preferably, it is 1 g / m or less. 2 More preferably, it is 80 g / m 2 The following is the result.
[0065] The thickness of the nonwoven fabric, woven fabric, porous membrane, or film (sheet) is usually 10 μm or more, preferably 50 μm or more, and usually 1 mm or less, preferably 500 μm or less.
[0066] <Adhesive body (pressure-bonded body)> An adhesive body according to one embodiment of the present invention is formed by bonding two or more substrates with the adhesive of the present invention, and is preferably a bonded body formed by bonding two or more substrates with the adhesive of the present invention, and more preferably a bonded body obtained by the method for manufacturing a bonded body described below. The number of substrates used in the adhesive body may be two or more. In this case, two or more substrates having different materials, shapes, etc. may be used, or two or more substrates having the same material, shape, etc. may be used.
[0067] The shape and size of the adhesive body are not particularly limited and may be appropriately selected depending on the desired application. The thickness of the adhesive is not particularly limited and may be appropriately selected depending on the application, but in the case of an adhesive of a nonwoven fabric or a porous membrane, it is usually 10 μm or more, preferably 50 μm or more, and usually 30 mm or less, preferably 25 mm or less.
[0068] The adhesive can be suitably used in applications where substrates containing resins, carbon materials, glass or metals have been used, and can be particularly suitably used in the medical field, electrical equipment field, semiconductor field and the like, and specifically can be suitably used as filters, various separators, clothing and the like.
[0069] The adhesive may contain one or more functional materials required for a desired application, such as foodstuffs, drugs (medicinal, agricultural, industrial), dyes, adsorbents, deodorants, fragrances, insect repellents, electronic device materials, enzymes, and catalysts. When the adhesive body contains such a functional material, even if the functional material has poor heat resistance, it is possible to obtain an adhesive body that makes use of the functions, properties, etc. of the functional material. For example, when a drug or the like is contained, an adhesive body with controlled sustained release or the like can be obtained.
[0070] <Manufacturing method of pressure-bonded body> The method for producing a pressure-bonded body according to one embodiment of the present invention (hereinafter also referred to as "the method") comprises the steps of: An adhesive containing an amorphous fluororesin; Carbon dioxide in liquid, gas-liquid mixture or near-liquid state The method includes the step of: The substrate is preferably made of a fluororesin. In this case, the present method can be said to be a novel method for processing substrates made of a fluororesin, which is difficult to process.
[0071] According to this method, a pressure-bonded body can be produced at a low cost in a short time at a temperature of about 50°C or less without applying high heat that melts the resin constituting the substrate, and since carbon dioxide does not basically remain in the obtained pressure-bonded body, a clean pressure-bonded body with excellent safety, controllability and productivity can be easily obtained. In addition, a pressure-bonded body having a desired shape with excellent mechanical strength and less susceptible to peeling between the substrates can be easily obtained. In particular, a pressure-bonded body can be obtained while maintaining the characteristics of the substrate (e.g., function, voids in the nonwoven fabric, fiber shape). Furthermore, according to this method, when manufacturing a pressure-bonded body containing a functional material to be used according to the desired application, even if the functional material has poor heat resistance, it is possible to obtain a pressure-bonded body that makes use of the functions, properties, etc. of the functional material.
[0072] It is not entirely clear why this method makes it possible to obtain a bonded body having the desired shape that has excellent mechanical strength and is less likely to peel off between the substrates, but it is thought that this is because when pressure is applied in the presence of carbon dioxide in a liquid, gas-liquid mixture, or near-liquid state, the amorphous fluororesin in the adhesive is plasticized by the carbon dioxide, and when pressure is applied in this plasticized state, the substrates can be bonded and joined while their shape is fixed in an interlocking state.
[0073] <Process 1> The step 1 is not particularly limited as long as it is a step of bonding two or more substrates under pressure in the presence of the adhesive and carbon dioxide in a liquid, gas-liquid mixture, or liquid-like state, and during this bonding, one or more functional materials required for the desired application may be used depending on the application. Examples of the functional materials include the same functional materials as those described in the adhesive section above.
[0074] In step 1, pressure may be applied by arranging an adhesive layer obtained from the adhesive in the form of a film, fiber, line, sphere (particle, dot), lattice, nonwoven fabric, or the like between the substrates, or pressure may be applied using a contact body in which the substrate and the adhesive are brought into contact, or a dried body obtained by drying the contact body. In the former case, for example, a method is used in which a film-like or fibrous adhesive layer is formed from the adhesive in advance, the adhesive layer is arranged between substrates, and pressure is applied, while in the latter case, for example, a method is used in which a substrate is immersed in the liquid adhesive, or the liquid adhesive is applied to a substrate in a desired shape (e.g., line, dot, or grid), and pressure is applied after volatilizing the solvent as necessary.
[0075] Step 1 may also be a step of forming a preliminary body by pressing one substrate and the adhesive in the presence of liquid, gas-liquid mixed, or liquid-like carbon dioxide, and then pressing the obtained preliminary body and a desired substrate to be pressed with the preliminary body, using the adhesive as necessary, in the presence of liquid, gas-liquid mixed, or liquid-like carbon dioxide.
[0076] In step 1, the substrate is compressed in the presence of carbon dioxide in a liquid state, a gas-liquid mixed state, or a state close to liquid. When carbon dioxide in a liquid state, a gas-liquid mixed state, or a state close to liquid is brought into contact with the substrate, the amorphous fluororesin in the adhesive is impregnated with carbon dioxide, which is thought to plasticize the amorphous fluororesin, and a compressed body can be produced without heating. In step 1, carbon dioxide in a subcritical or supercritical state may be used, but carbon dioxide in a liquid state or a gas-liquid mixed state is preferred from the viewpoints that the pressing force can be reduced and pressure bonding can be performed without using a device having a heating mechanism, etc. Also, since gaseous carbon dioxide is considered to hardly plasticize the base material or to require a considerable amount of time for plasticization, carbon dioxide in a liquid state or a gas-liquid mixed state is preferred from the viewpoints that the base material can be plasticized quickly, etc.
[0077] Specifically, the step 1 is preferably carried out by introducing liquid or gaseous carbon dioxide into the system. That is, specifically, the step 1 is preferably the following step 1a or 1b. Step 1a: A step of contacting a laminate having an adhesive layer obtained from the adhesive between substrates with liquid or gaseous carbon dioxide and applying pressure. Step 1b: A step of contacting a contact body obtained by contacting a substrate with the adhesive or a dried body obtained by drying the contact body with liquid or gaseous carbon dioxide and applying pressure.
[0078] When introducing liquid or gaseous carbon dioxide into the system, the order in which the substrate, adhesive, and carbon dioxide are introduced into the system is not particularly limited. For example, the substrate and adhesive may be introduced into a system filled with carbon dioxide, but it is preferable to introduce carbon dioxide into the system into which the substrate and adhesive have been introduced. When introducing liquid carbon dioxide, the compression step for liquefaction can be omitted compared to when introducing gaseous carbon dioxide, and therefore the compressed body can be manufactured in a short time. On the other hand, when gaseous carbon dioxide is introduced, the process is easier than when liquid carbon dioxide is introduced, and a pressure pump may be unnecessary, allowing the device to be simplified. When gaseous carbon dioxide is introduced, the introduced carbon dioxide is usually pressurized to liquefy the carbon dioxide. In this case, it is not necessary to liquefy all of the introduced carbon dioxide, and it is sufficient to liquefy at least a portion of it.
[0079] The amount of carbon dioxide introduced is not particularly limited, but when gaseous carbon dioxide is introduced and compression is performed at a temperature of 31°C (the critical temperature of carbon dioxide) or higher, carbon dioxide is introduced so that the density of carbon dioxide during compression is 0.4 g / mL or higher (about half the density of liquid carbon dioxide).
[0080] The surface pressure during pressure bonding in step 1 may be appropriately selected depending on the type and amount of the base material used, the desired shape of the pressure-bonded body, etc., but is preferably 4 MPa or more, more preferably 5 MPa or more, and there is no particular upper limit, but it is, for example, 50 MPa or less. The surface pressure is the sum of the pressure of the carbon dioxide introduced into the system and the pressing pressure.
[0081] The pressing time during pressure bonding in step 1 may be appropriately selected depending on the type and amount of the base material and adhesive used, the surface pressure and temperature during pressure bonding, etc., but is preferably 0.2 seconds or more, more preferably 1 second or more, and is preferably 15 minutes or less, more preferably 5 minutes or less.
[0082] The temperature during bonding in step 1 may be appropriately selected depending on the type and amount of base material and adhesive used, the desired shape of the bonded body, etc., but since the present method allows the desired bonded body to be obtained without applying heat, the temperature is usually 0°C or higher, preferably 20°C or higher, and usually 40°C or lower, preferably 30°C or lower, in order to more effectively exert this effect.
[0083] Step 1 may be carried out in a sealed container capable of reducing the volume, or may be carried out using an open pressing device. The sealed container may, for example, be a container having an inlet for introducing liquid or gaseous carbon dioxide into the sealed space and an outlet for carbon dioxide, and having a member such as a piston that can reduce the volume of the sealed container to press the substrate.
[0084] When an open pressing device is used, the object to be treated can be treated in a spot manner without using a large treatment container that covers the entire substrate to be treated. For example, the substrate can be sent out and pressed repeatedly in a different position, or a roller can be used instead of a piston to press the substrate, thereby continuously producing pressed bodies.
[0085] Furthermore, according to one embodiment of the present invention, unlike a pressure-bonded body obtained by thermal fusion, after carrying out step 1, a secondary processing can be carried out in which the obtained pressure-bonded body is further pressure-bonded to another substrate. EXAMPLES
[0086] Next, one embodiment of the present invention will be described in more detail with reference to examples, but the present invention is not limited to these.
[0087] [Example 1] A nonwoven fabric made of PTFE nanofibers with an average fiber diameter of 900 nm (manufactured by ZEUS Industrial Products, Inc., basis weight: 24 g / m 2 The substrate was prepared by punching a 19 mm diameter circular piece of aluminum foil (thickness: 70 μm) into a circular shape. Furthermore, Cytop (AGC Corporation, CTL-809M) was cast into a film shape using a doctor blade, and the solvent was then evaporated to produce a fluororesin film (thickness: 50 μm) to be used as the adhesive layer.
[0088] Five substrates, one fluororesin film for the adhesive layer, and five substrates were placed in this order in a sealable container (diameter: φ20 mm, container described in JP 2018-099885 A) having a piston, a carbon dioxide inlet, and a carbon dioxide outlet. Carbon dioxide equivalent to the vapor pressure of carbon dioxide (cylinder pressure: 6 MPa) was introduced therein at room temperature (25 ° C), the piston was lowered to reduce the volume in the container (while liquefying carbon dioxide), and a pressure of 300 N (about 1 MPa) was applied for 10 seconds to compress the space between the substrates. After that, the carbon dioxide was instantly discharged while maintaining the pressure, and then the pressure was released, and the pressure-bonded body (φ20 mm) was removed from the container. A pressure-bonded body in which a nonwoven fabric made of PTFE nanofiber was bonded by amorphous fluororesin was formed.
[0089] <Peel strength test> As the mechanical properties of the obtained pressure-bonded body, a universal tensile tester (EZ-test, manufactured by Shimadzu Corporation) was used to measure the average peel strength (N / 10mm) of the pressure-bonded body at a displacement of 5 to 10mm (5 to 10 seconds after tearing) when the pressure-bonded body was torn in the pressure-bonding direction (a tensile load was applied in the direction perpendicular to the adhesive surface) at a speed of 1mm / s. When the peel strength was 0.2N / 10mm or more, it was evaluated as having adhesiveness (○), and when the peel strength was less than 0.2N / 10mm, it was evaluated as not having adhesiveness (×). The results are shown in Table 1.
[0090] In Example 1, the two substrates that are in contact with the fluororesin film for the adhesive layer are bonded together. In other words, the peel strength is the peel strength between the two substrates that are in contact with the fluororesin film for the adhesive layer. When the substrates were used one by one, the peel strength could not be accurately measured, so in Example 1, five substrates were used.
[0091] [Example 2] A substrate similar to that prepared in Example 1 was immersed in Cytop (CTL-809M) for 10 seconds, removed from the solution, and then dried to obtain a substrate with a fluororesin. Except for stacking 10 of the obtained substrates with fluororesin and placing them in a container, a pressure-bonded body was produced in the same manner as in Example 1. Except for using the obtained pressure-bonded body, a peel strength test was carried out in the same manner as in Example 1. The results are shown in Table 1.
[0092] [Comparative Example 1] A laminate (without CO2) was produced in the same manner as in Example 1, except that carbon dioxide was not introduced. A peel strength test was carried out in the same manner as in Example 1, except that the obtained laminate (without CO2) was used. The results are shown in Table 1.
[0093] [Comparative Example 2] A laminate (without CO2) was produced in the same manner as in Example 2, except that carbon dioxide was not introduced. A peel strength test was carried out in the same manner as in Example 1, except that the obtained laminate (without CO2) was used. The results are shown in Table 1.
[0094] [Comparative Example 3] A laminate was produced in the same manner as in Example 1, except that a PTFE film (Valqua Corporation, VALFLON #7900, thickness: 100 μm) was used as the adhesive layer. A peel strength test was carried out in the same manner as in Example 1, except that the obtained laminate was used. The results are shown in Table 1.
[0095] [Comparative Example 4] A laminate was produced in the same manner as in Example 1, except that an ETFE film (manufactured by Daikin Industries, Ltd., Neoflon ETFE EF-0100, thickness: 100 μm) was used as the adhesive layer. A peel strength test was carried out in the same manner as in Example 1, except that the obtained laminate was used. The results are shown in Table 1.
[0096] [Comparative Example 5] A laminate was produced in the same manner as in Example 1, except that a PFA film (manufactured by Daikin Industries, Ltd., Neoflon PFA AF-0100, thickness: 100 μm) was used as the adhesive layer. A peel strength test was carried out in the same manner as in Example 1, except that the obtained laminate was used. The results are shown in Table 1.
[0097] [Comparative Example 6] A laminate was produced in the same manner as in Example 1, except that a PVDF film (Denka DX Film, manufactured by Denka Co., Ltd., thickness: 40 μm) was used as the adhesive layer. A peel strength test was carried out in the same manner as in Example 1, except that the obtained laminate was used. The results are shown in Table 1.
[0098] [Comparative Example 7] A laminate was produced in the same manner as in Example 1, except that an FEP film (manufactured by Daikin Industries, Ltd., Neoflon FEP NF-0100, thickness: 100 μm) was used as the adhesive layer. A peel strength test was carried out in the same manner as in Example 1, except that the obtained laminate was used. The results are shown in Table 1.
[0099] [Table 1]
[0100] [Example 3] A bonded body was produced in the same manner as in Example 1, except that a nonwoven fabric made of liquid crystal polymer fibers (Veculus MBBK11F, Kuraray Co., Ltd.) was used instead of the nonwoven fabric made of PTFE nanofibers. The adhesiveness between the nonwoven fabrics in the obtained pressure-bonded body was measured in the same manner as in Example 1, using a universal tensile tester (EZ-test, manufactured by Shimadzu Corporation) to measure the average peel strength (N / 10 mm) of the pressure-bonded body at a displacement of 5 to 10 mm (5 to 10 seconds after tearing) when the pressure-bonded body was torn in the pressure-bonding direction (a tensile load was applied in the direction perpendicular to the adhesive surface) at a speed of 1 mm / s. When the peel strength was 0.2 N / 10 mm or more, it was evaluated as having adhesiveness (○), and when the peel strength was less than 0.2 N / 10 mm, it was evaluated as not having adhesiveness (×). The results are shown in Table 2.
[0101] [Example 4] A bonded body was produced in the same manner as in Example 1, except that a glass fiber cloth (ATG26100-1, manufactured by Sakai Sangyo Co., Ltd.) was used instead of the nonwoven fabric made of PTFE nanofiber. The adhesiveness between the cloths in the obtained bonded body was evaluated in the same manner as in Example 3. The results are shown in Table 2.
[0102] [Example 5] A bonded body was produced in the same manner as in Example 1, except that a carbon fiber cloth (EC-CC1-060, manufactured by Electro Chem) was used instead of the nonwoven fabric made of PTFE nanofiber. The adhesiveness between the cloths in the obtained bonded body was evaluated in the same manner as in Example 3. The results are shown in Table 2.
[0103] [Example 6] A bonded body was produced in the same manner as in Example 1, except that a stainless steel fiber cloth (SUS304 mesh 400-023, manufactured by NBC Meshtec Co., Ltd.) was used instead of the nonwoven fabric made of PTFE nanofiber. The adhesiveness between the cloths in the obtained bonded body was evaluated in the same manner as in Example 3. The results are shown in Table 2.
[0104] [Comparative Example 8] A laminate (without CO2) was produced in the same manner as in Example 3, except that carbon dioxide was not introduced. The adhesion between the nonwoven fabrics in the obtained laminate was evaluated in the same manner as in Example 3. The results are shown in Table 2.
[0105] [Comparative Example 9] A laminate (without CO2) was produced in the same manner as in Example 4, except that carbon dioxide was not introduced. The adhesiveness between the cloths in the obtained laminate was evaluated in the same manner as in Example 3. The results are shown in Table 2.
[0106] [Comparative Example 10] A laminate (without CO2) was produced in the same manner as in Example 5, except that carbon dioxide was not introduced. The adhesiveness between the cloths in the obtained laminate was evaluated in the same manner as in Example 3. The results are shown in Table 2.
[0107] [Comparative Example 11] A laminate (without CO2) was produced in the same manner as in Example 6, except that carbon dioxide was not introduced. The adhesiveness between the cloths in the obtained laminate was evaluated in the same manner as in Example 3. The results are shown in Table 2.
[0108] [Table 2]
[0109] In the bonded bodies obtained in the examples, the substrates in contact with the adhesive layer were bonded with sufficient strength, and an adhesive body having the desired shape (a cylindrical shape with a diameter of 20 mm in the above tests) without fraying of fibers was obtained.
Claims
1. An adhesive comprising an amorphous fluororesin, An adhesive for bonding substrates (excluding carbon materials) in the presence of carbon dioxide in liquid or gas-liquid mixed state and in the absence of organic solvents.
2. The adhesive of claim 1 , which is an adhesive for bonding at a temperature below the temperature at which the adhesive melts.
3. 3. The adhesive according to claim 1, wherein the amorphous fluororesin is a fluoropolymer having a fluorinated aliphatic ring (which may have an ether bond).
4. The adhesive described in any one of claims 1 to 3, wherein the adhesive is a solid adhesive selected from a film-like, fibrous, line-like, particle-like, lattice-like or nonwoven fabric-like adhesive.
5. The adhesive described in any one of claims 1 to 4, wherein the substrate is at least one selected from a nonwoven fabric, a woven fabric, a porous membrane, and a fiber.
6. A bonded structure in which two or more substrates are bonded with the adhesive according to any one of claims 1 to 5.
7. The adhesive of claim 6 , wherein at least one of the substrates is a nonwoven fabric, a woven fabric, a porous membrane, or a fiber.
8. Two or more substrates, An adhesive containing an amorphous fluororesin; Carbon dioxide in liquid or gas-liquid state A method for producing a pressure-bonded body, comprising step 1 of performing pressure bonding in the presence of and in the absence of an organic solvent, and not including a step of kneading the base material and the adhesive.
9. The step 1 comprises: Step 1a of contacting a laminate having an adhesive layer obtained from the adhesive between substrates with liquid or gaseous carbon dioxide and applying pressure; or A step 1b of contacting a contact body obtained by contacting a substrate with the adhesive or a dried body obtained by drying the contact body with liquid or gaseous carbon dioxide and applying pressure. The method for producing a pressure-bonded body according to claim 8,
Citation Information
Patent Citations
Method for gas fusion of heat fusible member together and gas fusion apparatus used for it
JP1998044244A
Preparation of pressure-sensitive adhesive, pressure- sensitive adhesive composition and method for forming stable dispersion of pressure-sensitive adhesive polymer
JP2000129241A
Plastic joining method, plastic joining apparatus, and plastic product joined by using the method
JP2006116803A
Optical element and method for manufacturing same
JP2007139971A
Method for producing amorphous fluorine-containing resin
JP2007153970A